Seismological research in Yunnan Province, China, and its tectonic implication between the Xianshuihe-Xiaojiang fault system and the Red River fault zone - Dong, Shaopeng; Han, Zhujun; Guo, Peng; Xie, Zhangdi; Yin, Xinzhong (Frontiers in Earth Science, 2023)
The tectonic crosscutting relationship between the two most tectonic important Xianshuihe-Xiaojiang fault system (XFS) and the Red River fault zone (RRF) is a key basic problem but it is controversial now. These obscure further leads to a hot argument about the geodynamic model of the southeast margin of the Tibetan Plateau. In order to answer whether the XFS has cut across the RRF and extended southwardly, multiple seismological methods, including seismic relocation, b-value analysis, seismic energy, density study, focal mechanism inversion, and regional stress field research, are applied in the Yunnan Province area, China, where the XFS and the RRF intersects with each other. The results comprehensively demonstrate that the southern segment of the XFS has not been affected by the RRF, and it has continued for a length after crossing the RRF, but the Dian Bien Phu fault zone should not be an extension fault of the XFS. Along the SW direction, starting from the middle segment of the XFS, and cutting across the Qujiang fault, Shiping-Jianshui fault zone, RRF, Ailaoshan fault zone, Wuliangshan fault zone, and the southern section of the Daluo fault, the belt should be treated as the eastern boundary of the clockwise rotational in geodynamics model of the Tibetan Plateau in this study area. Based on these conclusion above and previous recognitions, a new geodynamic evolution model is proposed.